God, gender, and family trauma : how rereading Genesis can be a revelation - Driver, Cory Thomas Pechan (Minneapolis : Fortress Press, 2025)
"Driver uses trauma-informed scholarship and Jewish midrash to invite readers into new understandings of Genesis. Viewing figures such as Sarah, Joseph, Tamar, and Dinah through this lens sheds valuable light on what the Bible can teach us about gender and family trauma. These ancient stories have implications for our own lives in ministry"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 13, 2025).
JSTOR
Keywords: Bible. -- Social scientific criticism; Gender identity in the Bible; Sex role -- Biblical teaching; Families -- Biblical teaching; Families -- Mental health; Identité de genre dans la Bible; Rôle selon le sexe -- Enseignement biblique; Familles -- Enseignement biblique; Electronic books